THE DESCRIPTIVE ANALYSIS OF LOCATION DETERMINATION FACTORS IN PROBIOTIC DRINK FACTORY - Utomo, Regina Dewiyanti; Dzune, Dzul Yaa; Yudhistira, Sang Arya Daffa Hadi (Journal of Digital Business and Innovation Management, 2023)
The main objective of an organization is to satisfy and delight customers with its product and services. Therefore, it becomes essential for an organization to have a strategy formulated around its manufacturing unit. A manufacturing unit is where all inputs, such as raw materials, equipment, and skilled labor, come together and manufacture products for customers. One of the most critical factors determining the success of the manufacturing unit is the location.Factory location determination is a business-critical strategic decision. Several factors determine the factory's location: competition, cost, and corresponding associated effects. The factory location is a scientific process utilizing various techniques. This study aims to analyze the factors for choosing the location of PT. XYZ, a probiotic drink factory in Indonesia, to give some knowledge and managerial contribution to operational management studies. This study uses a descriptive qualitative method. The data collection method is collecting primary and secondary data such as the company's website, public research, and observation about factory location selection. The results of the analysis in this study show that the factors considered in choosing factory location are: 1) availability and location of resources and raw materials, (2) distance to target markets, (3) ease of distribution, (4) availability of labor, and (5) expansion opportunities.